2019
DOI: 10.3390/electronics8091031
|View full text |Cite
|
Sign up to set email alerts
|

High-Density EEG Signal Processing Based on Active-Source Reconstruction for Brain Network Analysis in Alzheimer’s Disease

Abstract: Alzheimer’s Disease (AD) is a neurological disorder characterized by a progressive deterioration of brain functions that affects, above all, older adults. It can be difficult to make an early diagnosis because its first symptoms are often associated with normal aging. Electroencephalography (EEG) can be used for evaluating the loss of brain functional connectivity in AD patients. The purpose of this paper is to study the brain network parameters through the estimation of Lagged Linear Connectivity (LLC), compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…The second measure from LORETA toolbox, named lagged linear connectivity, measures the statistical linear dependence between cortical source activities after the instantaneous zero-lag contribution has been removed, and therefore eliminates volume conduction effect (Pascual-Marqui, 2007b ; Pascual-Marqui et al, 2011 ). Lagged linear connectivity measure, as estimated by LORETA software, has been successfully employed in several EEG studies on functional cortical connectivity in AD patients (Babiloni et al, 2018a ,b; Foresta et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The second measure from LORETA toolbox, named lagged linear connectivity, measures the statistical linear dependence between cortical source activities after the instantaneous zero-lag contribution has been removed, and therefore eliminates volume conduction effect (Pascual-Marqui, 2007b ; Pascual-Marqui et al, 2011 ). Lagged linear connectivity measure, as estimated by LORETA software, has been successfully employed in several EEG studies on functional cortical connectivity in AD patients (Babiloni et al, 2018a ,b; Foresta et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…As for Alzheimer's Disease, brain networks are characterized by a weakening of the small-world properties as compared with healthy subjects [21][22][23]. Moreover, studies which compared healthy people, MCI, and AD patients have shown that MCI topological properties are intermediate [24][25][26]. Extensive reviews about graph theory applied to functional connectivity analysis in AD are provided in [27][28][29].…”
Section: Related Workmentioning
confidence: 99%
“…Frequently, it is used in the evaluation of Alzheimer's disease progress or even in its prognosis, since the brain activation related to cognitive performance is commonly altered in the disease's progression [63]. As such, eLORETA and connectivity analysis has been adopted for Alzheimer's disease diagnosis [64,65]. Another interesting approach is the use of ESI in localizing the origin of epileptic spikes using the differences created by non-Rapid Eye Movement (NREM) and Rapid Eye Movement (REM) sleep [66].…”
Section: Clinical Applicationsmentioning
confidence: 99%